Pengaruh Gaya Kepemimpinan Transformasional dan Iklim Organisasi terhadap Komitmen Organisasi - Endang Widyastuti; Muhammad Untung Manara (University of Merdeka Malang, 2014)
This study aimed to determine the effect of transformational leadership style and organizational climate on organizational commitment. Subjects were employees and lecturers at the University of Setia Budi Surakarta as many as 65 people. Data analysis used regression analysis techniques. Analisisis results showed a correlation coefficient (R) of 0.760 with F of 42.386 p = 0.000 (p 0.01) which means that there was a highly significant correlation between transformational leadership and organizational climate on organizational commitment. Determinant coefficient (R2) of 57.8%, this indicates that the variables of transformational leadership and organizational commitment affected organizational climate by 57.8% and 42.2% were influenced by other variables.